Minimal Neural Recruitment from Stevens Coding and Fechner Decoding in the Brain - Pradhan, Rajat Kumar (NeuroQuantology, 2017)
The psychophysical perceptual process can be taken to occur in two steps. The first one, from sensation to the generation of the neural correlate by population coding is assumed to obey Stevens' power law, while the second one, the decoding from the neural correlate to perception is postulated to obey Fechner's logarithmic law. This is shown to lead to the Complete form of Fechner's Law (CFL) as proposed by Nutting more than a hundred years back. The Minimal Neural Recruitment (MNR) for perception is calculated to be just a pair. The phenomenon of perceptual saturation is also discussed within the proposed model.